2020
DOI: 10.1371/journal.pone.0236413
|View full text |Cite
|
Sign up to set email alerts
|

Aortic stiffness—Is kynurenic acid a novel marker? Cross-sectional study in patients with persistent atrial fibrillation

Abstract: Objective Although a number of modifiable and non-modifiable causes were implicated in arterial stiffness, its pathogenesis remains elusive, and very little is known about aortic elasticity in supraventricular arrhythmias. The potential role of disturbed kynurenine metabolism in the pathogenesis of cardiovascular disease has been recently suggested. Thus, we studied the correlations of aortic stiffness and echocardiographic parameters with biochemical markers and serum level of kynurenic acid (KYNA), an endoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 64 publications
0
11
0
Order By: Relevance
“…Although 3-HAA was elevated in advanced atherosclerosis and correlated with decreased ankle-brachial index, it did not show increased odd ratio for advanced atherosclerosis ( 73 ). In atrial fibrillation increased KYNA was associated with raised aortic stiffness ( 90 ), but KYNA was not correlated with carotid intima-media thickness in chronic kidney disease ( 49 , 81 ).…”
Section: Kynurenine Pathway Metabolites As Potential Clinical Biomark...mentioning
confidence: 99%
“…Although 3-HAA was elevated in advanced atherosclerosis and correlated with decreased ankle-brachial index, it did not show increased odd ratio for advanced atherosclerosis ( 73 ). In atrial fibrillation increased KYNA was associated with raised aortic stiffness ( 90 ), but KYNA was not correlated with carotid intima-media thickness in chronic kidney disease ( 49 , 81 ).…”
Section: Kynurenine Pathway Metabolites As Potential Clinical Biomark...mentioning
confidence: 99%
“…However, its presence in the periphery is poorly studied, being reported in the heart, kidneys, liver, and endothelium [ 4 , 5 , 31 ]. Hypoglycemia and anoxia are factors that control the KYNA levels in serum, when produced by the endothelium [ 5 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…The PAr-index has been associated with future stroke in a population study [ 18 ] but has never been studied in a stroke population nor in the context of stroke recurrence. The role of KA in stroke recurrence is not clear, but KA has been found to be associated with coronary events [ 39 , 40 ] and aortic stiffness, which in turn is associated with atrial fibrillation [ 41 ]. In a recent study, Baumgarten et al found that the branch of the kynurenine pathway, leading to the formation of KA, was downregulated in atherosclerotic plaques, and this downregulation was associated with an increased risk of cerebrovascular events [ 19 ].…”
Section: Discussionmentioning
confidence: 99%